Mass shootings : media, myths, and realities - Schildkraut, Jaclyn; Elsass, H. Jaymi (Santa Barbara, California : Praeger, an imprint of ABC-CLIO, LLC, 2016)
This book provides readers and researchers with a critical examination of mass shootings as told by the media, offering research-based, factual answers to oft-asked questions and investigating common myths about these tragic events. When a mass shooting happens, the news media is flooded with headlines and breaking information about the shooters, victims, and acts themselves. What is notably absent in the news reporting are any concrete details that serve to inform news consumers how prevalent these mass shootings really are (or are not, when considering crime statistics as a whole), what legitimate causes for concern are, and how likely an individual is to be involved in such an incident. Instead, these events often are used as catalysts for conversations about larger issues such as gun control and mental health care reform. What critical points are we missing when the media focuses on only what "people want to hear"? This book explores the media attention to mass shootings and helps readers understand the problem of mass shootings and public gun violence from its inception to its existence in contemporary society. It discusses how the issue is defined, its history, and its prevalence in both the United States and other countries, and provides an exploration of the responses to these events and strategies for the prevention of future violence. The book focuses on the myths purported about these unfortunate events, their victims, and their perpetrators through typical U.S. media coverage as well as evidence-based facts to contradict such narratives. The book's authors pay primary attention to contemporary shootings in the United States but also discuss early events dating back to the 1700s and those occurring internationally. The accessible writing enables readers of varying grade levels, including laypersons, to gain a more in-depth -- and accurate -- understanding of the context of mass shootings in the United States. As a result, readers will be better able to contribute to meaningful discussions related to mass shooting events and the resulting responses and policies. -- Provided by publisher.
Claims making and agenda setting: how myths become realities -- What is a "mass shooting"? -- A history of public mass shootings -- Mass shootings by the numbers -- The "usual suspects" as causal factors -- Mass shootings around the globe -- Preventing mass shootings -- Mass shootings in a mediatized society -- Mass shootings today and beyond.
Includes bibliographical references (pages 163-229) and index.
Keywords: Mass murder; Firearms; Firearms and crime; Violent crimes; Murder in mass media; Violence in mass media